The Effect of Snakes and Ladder Media on Dribbling Skills in Basketball Extracurricular Students (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
The aim of this study was to find out how much influence the use of snakes and ladders media games had in improving students' dribbling skills in basketball games. With 24 participants consisting of 19 students and 5 female students at public senior high school 5 Luwu, the research method used experiment with pre-test and post-test one group design. By giving treatment of snakes and ladders media game in the learning process. The research process lasted for 5 weeks with the results of data analysis showing that the average score obtained by students when the pre-test was carried out was in the less category with a large percentage of 50% with 12 students and the post-test was in the sufficient category with a large percentage of 42% with 10 students. So it can be concluded that the use of snakes and ladders media has a significant effect on the results of students' basic basketball dribbling skills. The data analysis technique used was the pre-test and post-test with the student's instrument sending the ball on a zig zag trajectory.